Pelatihan Pengelasan SMAW Kepada Para Remaja Untuk Meningkatkan Skill dan Pengetahuan - Dani, Dani Hari Tunggal Prasetiyo; Mas Ahmad Baihaqi; Alief Muhammad; Djoko Wahyudi; Indah Noor Dwi Kusuma Dewi; Hartawan Abdillah; Wahyu Nur Achmadin (Fakultas Teknik, Universitas PGRI Banyuwangi, 2023)
Population growth that is not matched by the availability of job vacancies can cause the unemployment rate to increase. Therefore efforts are needed to reduce the number of unemployed through training activities. Training activities are carried out to equip youth with skills and knowledge. One of the knowledge and skills that can be given to youth is welding skills. Tamansari Village, which is located in Dringu District, Probolinggo Regency, has the potential of human resources. Therefore, efforts are needed to equip young people in Tamansari village with skills and knowledge, one of which is welding skills. The results of the community service activities that have been carried out were followed enthusiastically by the participants. Participants can understand the theory that has been presented and followed by welding skills using the SMAW welding method.